Angiotensin II and ischemic preconditioning synergize to improve mitochondrial function while showing additive effects on ventricular post-ischemic recovery - Nuñez, Rebeca E. (2014)
Recent studies indicate that the cardioprotective effects of ischemic preconditioning (IPC) against sustained ischemia/reperfusion (IR) can be replicated by angiotensin II (Ang II). However, it is not clear whether IPC and Ang II-induced preconditioning (APC) act through similar mechanisms or synergize to enhance cardioprotection. In this study, Langendorff-perfused rat hearts were subjected to IPC, APC or their combination (IPC/APC) followed by IR. IPC and less potently APC, significantly increased the percent recovery of the left ventricular developed-pressure, the first derivative of developed pressure and the rate pressure product compared to control. Furthermore, the post-ischemic recovery of the heart was significantly higher for IPC/APC compared to IPC or APC. The improvements in cardiac function by IPC, APC and IPC/APC were associated with similar reductions in LDH release and infarct size. However, a significant improvement in mitochondrial respiration was observed with IPC/APC. The post-ischemic recovery observed with APC and IPC/APC was inhibited by treatment with losartan, an Ang II type-1 receptor blocker, during the preconditioning phase but not by chelerythrine, a pan-PKC inhibitor. Both drugs, however, abolished the enhanced mitochondrial respiration by IPC/APC. Altogether, these results indicate that APC and IPC interact through mechanisms that enhance cardioprotection by affecting cardiac function and mitochondrial respiration.